PERANCANGAN APLIKASI PENGAMANAN INFORMASI TEKS DENGAN MENGGUNAKAN ALGORITMA KRIPTOGRAFI ALPHA-QWERTY REVERSE - Muhammad Eka Putra; Suroso Suroso; Ade Wasti (Jurnal Elektro dan Telekomunikasi Terapan (e-Journal), 2017)
Alpha - qwerty reverse is one part of the classical cryptographic algorithm that serves as the security of infor mation by encoding to information. The process of encryption of that information is encrypted and description. Alpha - qwerty reverse algorithm is a development of vigenere cipher cryptographic algorithms. Alpha - qwerty reverse differences in terms of number of characters that are more than vigenere cipher in which the alpha - qwerty reverse using 92 characters while vigenere cipher uses only 26 characters. Moreover, in terms of the use of character is also different. In vigenere cipher, the characters used an a lphabet sequence either in the original message (plaintext), a key or an encrypted message (ciphertext) whereas the alpha - qwerty reverse using the alphabetical order of the plaintext and key keyboard. Therefore, in this study will design a security applica tion that is text information with the cryptographic algorithm of alpha - qwerty reverse using a eclipse software. The aim of designing applications, namely to secure the important text information contained in the mobile phone based on android with the purp ose of storing or transmitting through a mobile phone communication service. From this study it can be concluded that alpha - qwerty reverse cryptographic algorithms can be implemented on the text information security applications designed and as the latest cryptographic algorithms to secure the information by generating a better level of security.